Galanin suppresses visceral afferent responses to noxious mechanical and inflammatory stimuli. Issue 2 (20th January 2020) - Taylor, Toni S.; Konda, Parvesh; John, Sarah S.; Bulmer, David C.; Hockley, James R. F.; Smith, Ewan St. John
Abstract: Galanin is a neuropeptide expressed by sensory neurones innervating the gastrointestinal (GI) tract. Galanin displays inhibitory effects on vagal afferent signaling within the upper GI tract, and the goal of this study was to determine the actions of galanin on colonic spinal afferent function. Specifically, we sought to evaluate the effect of galanin on lumbar splanchnic nerve (LSN) mechanosensitivity to noxious distending pressures and the development of hypersensitivity in the presence of inflammatory stimuli and colitis. Using ex vivo electrophysiological recordings we show that galanin produces a dose‐dependent suppression of colonic LSN responses to mechanical stimuli and prevents the development of hypersensitivity to acutely administered inflammatory mediators. Using galanin receptor (GalR) agonists, we show that GalR1 activation, but not GalR2/3 activation, suppresses mechanosensitivity. The effect of galanin on colonic afferent activity was not observed in tissue from mice with dextran sodium sulfate‐induced colitis. We conclude that galanin has a marked suppressive effect on colonic mechanosensitivity at noxious distending pressures and prevents the acute development of mechanical hypersensitivity to inflammatory mediators, an effect not seen in the inflamed colon. These actions highlight a potential role for galanin in the regulation of mechanical nociception in the bowel and the therapeutic potential of targeting galaninergic signaling to treat visceral hypersensitivity. Abstract : Galanin inhibits lumbar splanchnic nerve activity in response to mechanical distension via GalR1 and also abolishes the mechanical hypersensitivity induced by inflammatory mediators. However, galanin loses this inhibitory effect in a model of colitis.